Tổng hợp xúc tác từ vật liệu nguồn mordenit ứng dụng cho quá trình nhiệt phân polystyren thu hồi đồng sản phẩm lỏng khí - Trúc Linh, Nguyễn Thị; Minh, Phan Nghĩa; Tuấn, Phan Đình (Vietnam Journal of Chemistry, 2015)
The catalysts used in the pyrolysis process of polystyrene were produced from natural mordenite by ion exchange method and impregnation in the molybdate salt solution. The IR results showed that the band absorption at 3613 cm-1 assigned to OH− stretching vibration (corresponding Lewis acid site) of MoO3/mordenite catalyst was stronger than that of mordenite catalyst. The GC-MS results indicated that the liquid pyrolyzates were mainly styrene and benzene derivatives. In case of using the mordenite catalyst, the percentage of styrene was 57.08 % which was higher around 1.79 % than the case of using MoO3/mordenite catalyst. However, presence of MoO3 in the catalyst made the properties of the liquid pyrolyzates change such as the percentage of benzene (3-nitropropyl) and benzene,1,1'-(3-methyl-1-propen) increasing upto 10.83 % and 5.52 %, respectively. The total amount of the compounds having 8 carbons in the liquid pyrolyzates was 62.47 % in case of using MoO3/mordenite catalyst, which was higher 4.05 % than in case of using mordenite catalyst. The GC-MS results indicated that the gas pyrolyzates were 40 % H2, 10 % CH4, 21 % (C2H4, C2H6) and 25 % (C3H6, C3H8) in case of using MoO3/mordenite catalyst and were 68 %H2 and around 31 % (C2H4, C2H6) when using another one.